Application and design method of dredging sludge ground treated via prefabricated radiant drain vacuum preloading. Issue 5 (4th May 2023) - Feng, Shuangxi; Lei, Huayang; Liu, Anyi; Dai, Shitao; Ma, Tianlu; Lei, Zheng
Abstract: The high-water-content sludge produced through dredging seriously restricts marine ecological environments. Vacuum preloading methods (involving prefabricated vertical drains (PVDs)) are widely used to dewater and consolidate sludge ground, but these methods require long treatment periods and have deprived reinforcement effects. To overcome the limitations of PVD vacuum preloading, a prefabricated radiant drain (PRD) vacuum preloading method is proposed is this study by adding a prefabricated horizontal drain (PHD) to the PVD framework. Physical model tests are conducted under PVD and PRD vacuum preloading conditions, and a large-strain three-dimensional finite element (FE) model is established and validated against the physical model test data. FE parametric analyses are also conducted to evaluate the key factors influencing the PRD, i.e., the PHD length and spacing. The results show that the reinforcement effect of PRD vacuum preloading is better than that of PVD vacuum preloading. The ground settlement effect increases as the PHD length increases and the PHD spacing decreases. The settlement and pore water pressure metrics show elliptical distributions with an increasing PHD length. Through this work, an applicable sludge ground treatment design procedure is suggested based on parametric analyses; these findings can provide a reference for designing sludge ground treatments in the future.